Internal Control And Organizational Culture in the Improvement of Managerial Performance - Rukmi Juwita; Mutimmatul Adzkhiyah (TRIKONOMIKA, 2017)
This research aimed to measure the influence of internal control and organizational culture in managerial performance. Data were obtained through questionnaires with sample of 46 from 84 SKPD in Banyumas Regency using purposive sampling technique. Data processing used is multiple linear regressions. The results showed that internal control and organizational culture simultaniously had a significant effect to managerial performance of government. Partially, internal control had significant effect while organizational culture had no significant effect on managerial performance of government. The implementation of internal control and organizational culture was good. Achievement of good managerial performance required good internal control to provide reasonable assurance on the achievement of organizational goals through effective and efficient activities, reliability of financial reporting, security of state assets and compliance with laws and regulations. Organizational culture became another factor that could improve managerial performance through fundamental values and passion in managing the organization.